Bimbingan dan Penyuluhan Dalam Mengoptimalkan Minat Siswa Lanjut Studi Perguruan Tinggi - Hardiansyah, Fadhil; Jannah, Ummi Rojatul; Rahmayanty, Dinny (Indonesian Journal of Educational Counseling, 2023)
Guidance and counseling is a process of assisting someone in solving and dealing with problems in their life through an extension worker, either by preventing problems from arising or by finding solutions to their problems. This study aims to determine guidance and counseling in optimizing students' interest in continuing their tertiary studies at the eleventh grade of Vocational High School PGRI 1 Transpram II Labuhan Ratu Lampung Timur. This type of research is field research, with the nature of qualitative descriptive research. This study uses interview data collection techniques, observation, and documentation. Interviews were conducted with the Head of the eleventh grade of Vocational High School PGRI 1 Transpram II, Deputy Student Affairs, Deputy Head of Curriculum, Counseling Teachers, eight students, and two alums of the eleventh grade of Vocational High School PGRI 1 Transpram II. All these data were analyzed deductively. Based on the results of research, guidance, and counseling in optimizing the interest of students continuing their tertiary studies at the eleventh grade of Vocational High School PGRI 1 Transpram II Labuhan Ratu Lampung Timur in its implementation uses orientation services, information services, placement, and distribution services, classical guidance services, and individual guidance services. Factors influencing students' interest in continuing their studies at tertiary institutions are support from the school, motivation, and support from the family.